2016
DOI: 10.1177/0300985816660746
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Producing Odontogenic Tumors of the Facial Skin in Three Cats

Abstract: Amyloid-producing odontogenic tumors (APOTs) of the facial skin were diagnosed in 3 domestic cats. The neoplasms had the histopathological characteristics of the odontogenic tumor. The neoplastic cells were present in irregular islands, strands, and sheets. The peripheral neoplastic cells of the islands and strands were arranged in a palisading fashion, while the central cells were polyhedral to stellate and randomly arranged. Multiple spherules of homogeneous eosinophilic material were closely apposed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
(45 reference statements)
0
6
1
Order By: Relevance
“…Odontogenic ameloblast-associated protein, the amyloid precursor protein of human CEOT, was not detected. In addition, neither sheathlin nor amelogenin, which were immunohistochemically detected in animal APABs in previous studies [ 17 , 26 ], were detected in all cases in this study.…”
Section: Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…Odontogenic ameloblast-associated protein, the amyloid precursor protein of human CEOT, was not detected. In addition, neither sheathlin nor amelogenin, which were immunohistochemically detected in animal APABs in previous studies [ 17 , 26 ], were detected in all cases in this study.…”
Section: Resultscontrasting
confidence: 90%
“…In this study, mass-spectrometry-based proteomic analysis extracted ameloblastin as a prime candidate for precursor protein of APAB, and immunohistochemistry showed evidence for the existence of ameloblastin in amyloid deposits of both cats and dogs. Several immunohistochemistry-based studies in canines and felines have shown that ameloblastin [ 17 , 26 , 28 ], sheathlin, and amelogenin [ 17 , 28 ] are present in amyloid deposits but are negative for antibodies to cytokeratins and vimentin [ 17 ]. The amyloid of APABs from a cat, dog, and Bengal tiger did not contain odontogenic ameloblast-associated protein-related peptides but rather an ameloblastin-like peptide; an N-terminal residue of ameloblastin was detected from collected amyloid deposits of these APAB cases [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, different amyloids were found in a variety of tumors. Different carcinomas have amyloid stroma [54,55], and odontogenic tumors are positive for thioflavin T and Congo Red staining and are also immunopositive for the enamel matrix protein ameloblastin [56,57,58]. Similarly, amyloid was reported in breast cancer tumors but was determined to be a localized amyloid light chain (AL) type (primary amyloidosis caused by ImG light-chain β-sheeting) [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some tissue-specific cancerous tumor types overproduce tissue-specific, aggregationprone proteins. For example, the amyloid in odontogenic tumors is immunopositive for the enamel matrix protein ameloblastin [15][16][17]. Unlike odontogenic tumors, the tumoral amyloidosis of bone is usually of β2M origin and almost always progresses to multiple myeloma [18].…”
Section: Introductionmentioning
confidence: 99%